Ethics of genomic passports: should the genetically resistant be exempted from lockdowns and quarantines? - Gyngell, Christopher (Journal of medical ethics, 2022)
Lockdowns and quarantines have been implemented widely in response to the COVID-19 pandemic. This has been accompanied by a rise in interest in the ethics of ‘passport’ systems that allow low-risk individuals greater freedoms during lockdowns and exemptions to quarantines. Immunity and vaccination passports have been suggested to facilitate the greater movement of those with acquired immunity and who have been vaccinated. Another group of individuals who pose a low risk to others during pandemics are those with genetically mediated resistances to pathogens. In this paper, we introduce the concept of genomic passports, which so far have not been explored in the bioethics literature. Using COVID-19 as an illustrative example, we explore the ethical issues raised by genomic passports and highlight differences and similarities to immunity passports. We conclude that, although there remain significant practical and ethical challenges to the implementation of genomic passports, there will be ways to ethically use them in the future.